Effect of Quarry Waste on Self-Compacting Concrete Containing Binary Cementitious Blends of Fly Ash and Cement - Baboo Rai; Sanjay Kumar; Kumar Satish (Advances in Materials Science and Engineering)
This paper presents the results of the experimental work conducted to study the effect of quarry waste on self-compacting concrete containing binary cementitious blends of fly ash and cement. For this purpose nine trial mixes were prepared, where the percentage replacement of river sand by quarry waste was 0%, 10%, 20%, 30%, 40%, 50%, 70%, and 100% to study the flowability characteristics of SCC. In all, 108 cube samples and 54 cylindrical samples were cast to study the strength parameters of SCC with and without quarry waste. The water to binder ratio was maintained at 0.36% while the dose of chemical admixture was 2.2% by weight of cement. For all trial mixes the fly ash percentage replacement to cement was kept constant at 30%. Based on the standard flowability test a visual stability index has been provided to all the trial mixes. Quarry waste replacement showed the desirable results that can suggest the usage in self-compacting concrete as well as in normally vibrated concrete.